Integration of smart watch and geographic information system (GIS) to identify post-earthquake critical rescue area part. II. Analytical evaluation of the system. (January 2021) - Hossain, M.S.; Chaitanya, K.; Bhattacharya, Y.; Numada, M.; Kamal, A.S.M.M.; Meguro, K.
Abstract: The efficient allocation of resources in the aftermath of an earthquake in an affected area largely depends on the identification of post-earthquake critical rescue area. This paper is the second part of the companion paper on the integration of smart watch and geographic information system (GIS) to identify post-earthquake critical rescue area. In the first paper, we proposed a new system through an application installed on a wearable device to dissipate the information of trapped victims called the Earthquake Emergency Micro Response System (EEMRS) Hossain et al. (2020) [27 ]. In the current paper an analytical model is developed to evaluate the effectiveness of it in the search and rescue (SAR) operations. The information dissemination formulation is postulated through observations and interactions with experts. The process of local first responders' immediate post-earthquake activities from dispatch to extricating the trapped victims at the affected area is carefully calibrated with the firefighter activities recorded in the aftermath of Kobe earthquake. Evaluation using the developed analytical method imply that the increase in use of smart watches in earthquake prone areas can significantly increase the extrication efficiency of firefighters. In addition, this proposed model can be used by emergency managers to know the robustness of their post-earthquake initial situation assessment techniques.